Romances nuevos y romances viejos Españoles e hispanoamericanos (COLIHUE, 1981)
Otros autores: MIO CID; LOPE DE VEGA; GONGORA, Luis de; QUEVEDO, Francisco de; ZORRILLA, José; RUBEN DARIO; IBARBOUROU, Juana de; MACHADO, Antonio; ALEIXANDRE, Vicente; GARCIA LORCA, Federico; HERNANDEZ, MIguel; CANE, Luis; FERNANDEZ MORENO, Baldomero; NALE ROXLO, Conrado; BERNARDEZ, Francisco Luis; CASTILLA, Luis; YUPANQUI, Atahualpa; OSTIZ, María